2022
DOI: 10.3389/fphar.2022.858348
|View full text |Cite
|
Sign up to set email alerts
|

Druggability of Voltage-Gated Sodium Channels—Exploring Old and New Drug Receptor Sites

Abstract: Voltage-gated ion channels are important drug targets because they play crucial physiological roles in both excitable and non-excitable cells. About 15% of clinical drugs used for treating human diseases target ion channels. However, most of these drugs do not provide sufficient specificity to a single subtype of the channels and their off-target side effects can be serious and sometimes fatal. Recent advancements in imaging techniques have enabled us for the first time to visualize unique and hidden parts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 141 publications
(201 reference statements)
1
14
0
Order By: Relevance
“…Pertinent to this reaction scheme is thus that the open-blocked Na V channels tend to be not closed unless the KB-R7943 molecule dissociates from the binding site(s). Meanwhile, the time-dependent block caused by this compound suggests that it preferentially binds to and blocks the open/inactivated state (conformation) of the Na V channels, thereby leading to a destabilization in open conformation [ 16 ]. Moreover, although the steady-state I-V relationship of I Na(T) was unaffected during the presence of KB-R7943, this compound diminished the strength of I Na(W) or I Na(R) evoked by respective ascending or descending V ramp .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pertinent to this reaction scheme is thus that the open-blocked Na V channels tend to be not closed unless the KB-R7943 molecule dissociates from the binding site(s). Meanwhile, the time-dependent block caused by this compound suggests that it preferentially binds to and blocks the open/inactivated state (conformation) of the Na V channels, thereby leading to a destabilization in open conformation [ 16 ]. Moreover, although the steady-state I-V relationship of I Na(T) was unaffected during the presence of KB-R7943, this compound diminished the strength of I Na(W) or I Na(R) evoked by respective ascending or descending V ramp .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in cultured hippocampal neurons, KB-R7943 exhibits neuroprotection from glutamate-induced excitotoxicity by blocking NMDA receptor-mediated activity (IC 50 = 13.4 μM) as well as by inhibiting complex I in the mitochondrial respiratory chain (IC 50 = 11.4 μM) [ 8 ]. Under this scenario, the inhibitory effect of this compound on the magnitude and gating of I Na could be of mechanistic, pharmacological, or even clinical relevance [ 15 , 16 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant step in this direction is represented by the recent boost of deep-learning-based approaches to predict protein structures, , as it has been observed that predicted models of Na v channels are quite close to cryo-EM structures . However, limited differences have been pointed out in specific protein domains, and further experimental and computational studies are necessary to understand their effects. , …”
Section: Discussionmentioning
confidence: 99%
“…These proteins were discovered by Hodgkin and Huxley and have since been studied by a variety of biophysical and biochemical techniques. Eukaryotic Na v s are composed of a large pore-forming α subunit and a smaller auxiliary β subunits [ 2 ]. The α subunit contains 24 transmembrane segments organized in four homologous but not identical domains (DI-DIV) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%